Social support and elementary school girls' readiness in facing menarche in the digital era - Khomsiah, Nurul Fitri; Amalia, Rize Budi; Utomo, Budi (Institute of Computer Science (IOCS), 2025)
Adolescent girls have wide access to menarche-related information in the digital era; however, the validity of the information they receive may vary and lead to unpreparedness in facing these changes. In this context, social support from parents, peers, and the surrounding environment becomes an important aspect in shaping adolescents' readiness to face menarche. This study aimed to determine the relationship between social support and adolescents’ readiness to face menarche in the digital era. This research used an observational analytic design with a cross-sectional approach. The study involved 102 female students from grades IV to VI at an elementary school in Surabaya, selected through a proportional random sampling. Data were collected using a questionnaire and analyzed using the chi-square test. The results showed that the majority of respondents (70.6%) received social support, especially informational support (78.4%), with mothers being the primary source of support (65 respondents), and TikTok as the most popular digital platform (39 respondents). Most respondents (79.4%) were categorized as ready to face menarche, with the readiness of pre-menarche students (83.1%) being higher than those who had already menstruated (73.0%). The chi-square test showed a significant relationship between social support and adolescents’ readiness to face menarche, with a p-value of 0.005 (p < 0.05). Social support plays an important role in increasing adolescents’ readiness to face menarche in the digital era. Therefore, the role of families, schools, and the social environment in providing education and emotional support is essential to help adolescents face menarche with greater confidence.